2018
DOI: 10.1016/j.cjtee.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of brain injuries associated with maxillofacial fractures and its fate in emergency Egyptian polytrauma patients

Abstract: PurposeMaxillofacial injuries are commonly encountered in the practice of emergency medicine. More than 50% of patients with these injuries have multisystem trauma that requires coordinated management between emergency physicians and surgical specialists in oral and maxillofacial surgery, otolaryngology, plastic surgery, ophthalmology, and trauma surgery. The aim of this study is to identify the patterns of brain injuries associated with maxillofacial trauma and its outcome.MethodsThis descriptive study (cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
5
21
0
Order By: Relevance
“…Moreover, often these fractures are in the mid-face area (the worst of the maxillofacial fractures) and are rarely in the low face area. EDHs are much less frequently associated with maxillofacial fractures and, generally, the mid-face area [ 77 , 78 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Moreover, often these fractures are in the mid-face area (the worst of the maxillofacial fractures) and are rarely in the low face area. EDHs are much less frequently associated with maxillofacial fractures and, generally, the mid-face area [ 77 , 78 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…1 Patients are prone to long-standing physical deformities, neurological impairment, prolonged management, and psychiatric morbidities. 2 4 The advent of advanced diagnostic modalities and surgical techniques has helped alleviate the otherwise devastating impact these patients may incur. However, the relatively frequent incidence coupled with the severity of injury still creates a prominent issue.…”
Section: Introductionmentioning
confidence: 99%
“…29 Other associated injuries were subarachnoid hemorrhage 13 (18.5%), subdural hematoma 13 (18.5%), extradural hematoma 10 (14.2 %), contusions 16 (22.8%) and pneumocephalus 11 (15.7%), a study done by Elbaih AH et al has shown that brain injuries are commonly associated injuries with maxillofacial trauma. 30,31…”
Section: Discussionmentioning
confidence: 99%